Competitiveness of ALS inhibitors resistant and susceptible biotypes of Greater Beggarticks (Bidens subalternans) - Lamego,F.P. (2011)
The continuous use of ALS-inhibiting herbicides has led to the evolution of herbicide-resistant weeds worldwide. Greater beggarticks is one of the most troublesome weeds found in the soybean production system in Brazil. Recently, a greater beggarticks biotype that is resistant (R) to ALS inhibitors due to Trp574Leu mutation in the ALS gene was identified. Also, the adaptive traits between susceptible (S) and R to ALS inhibitors biotypes of greater beggarticks were compared. Specifically, we aimed to: (1) evaluate and compare the relative growth rates (RGR) between the biotypes; (2) analyze the seed germination characteristics of R and S biotypes under different temperature conditions; and (3) evaluate their competitive ability in a replacement series study. The experiments were conducted at the University of Arkansas, USA, in 2007 and at Universidade Federal do Rio Grande do Sul (Federal University of Rio Grande do Sul), Brazil, in 2008. Plant proportions for replacement series studies were respectively 100:0, 75:25, 50:50, 25:75 and 0:100, with a total population of 150 plants m-2. There was no difference in RGR between R and S biotypes. The R-biotype germination rate was lower than that of the S biotype. However, at low temperature conditions (15 ºC), the reverse was observed. In general, there is no difference in the competitive ability between R and S greater beggarticks biotypes.